1997
DOI: 10.1023/a:1007936930354
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pea (Pisum sativum), faba bean (Vicia faba) and soybean (Glycine max) seeds were characterized, and protein isolates were prepared following an isoelectric point precipitation procedure. Soybean seeds showed the highest protein content (36.7%) and carbohydrate was the major constituent in the pea (59.4%) and the faba bean seeds (52.1%). Protein contents were higher than 80% in all the protein isolates. The amino acid contents in the protein isolates were, in general, higher than those in their own starting see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(44 citation statements)
references
References 10 publications
7
36
1
Order By: Relevance
“…The protein isolates are rich in leucine the values were 8.8 and 8.9 g/16 g N for CPII and CPIM respectively. This result was similarly reported [15] 8.0 and 8.4 g/16 g N for pea and faba bean proteins isolates. Methionine was the most essential amino acids in both protein isolates (CPII and CPIM).…”
Section: Amino Acid Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…The protein isolates are rich in leucine the values were 8.8 and 8.9 g/16 g N for CPII and CPIM respectively. This result was similarly reported [15] 8.0 and 8.4 g/16 g N for pea and faba bean proteins isolates. Methionine was the most essential amino acids in both protein isolates (CPII and CPIM).…”
Section: Amino Acid Compositionsupporting
confidence: 89%
“…Preparation of cowpea protein isolate (CPI) by isoelectric precipitation (CPII): CPII was prepared from cowpea seed flour as shown in Figure 2 following the method described by Thompson [with slight modifications [14] [15].…”
Section: Methodsmentioning
confidence: 99%
“…FAC of pea protein and chickpea flour were 79% and 87% (w/w) respectively. All the FACs measured in this study were lower than for soy protein concentrate (SPC) or soy protein isolate (SPI) (FAC= 218-251 % reported by L'hocine et al, 2006), but they are comparable with FACs of soy flour, SPC and SPI ranging from 84.4 % to 154.5 % (w/w), reported by Lin et al, 1974. Fernandez-Quintela et al (1997 also reported higher FAC of 160 % and 120 % (w/w) for faba bean isolate and pea protein isolate, respectively.…”
Section: Functional Properties Of Pulse Ingredientscontrasting
confidence: 47%
“…Failure of a protein to bind water could lead to brittle and dry characteristics of the product [5]. WHC values for pulse protein concentrates, such as pea, faba bean, lentil and chickpea, have been determined by various groups [66,89,90] and fall in the range of 0.6-4.9 g/g, suggesting that both pulse genotype and manner of processing could impact values. For instance, Kaur and Singh [89] found that protein isolates prepared by kabuli chickpea cultivars (PBG-1, PDG-4, PDG-3, GL769 and GPF-2) produced significantly lower WHC than desi chickpea (L550) (p<0.05) which clearly indicates the impact of different cultivars in assessing functionality.…”
Section: Oil Holding and Water Hydration Capacities (Ohc Whc)mentioning
confidence: 99%